2013
DOI: 10.1111/his.12129
|View full text |Cite
|
Sign up to set email alerts
|

Ductal carcinoma of the prostate shows a different immunophenotype from high grade acinar cancer

Abstract: These results suggest that the hormone related molecular pathways that drive cancer progression might be different in AC and DC. The decrease in steroid synthesis related enzymes, together with up-regulation of the BCAR1-Src pathway, emphasizes the biological particularities of DC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…In a recent cancer registry study, the disease‐specific mortality of DAC was found to be 12%, as compared with 4% for patients with acinar prostate cancer. In this series, metastases were seen in 11% of DACs, as compared with 4% of acinar prostate cancers . For these reasons, it is recommended that prostate cancer showing any component of DAC should be treated as high‐risk disease, owing to its potential to spread locally and the likelihood of the development of metastatic disease …”
Section: Discussionmentioning
confidence: 88%
“…In a recent cancer registry study, the disease‐specific mortality of DAC was found to be 12%, as compared with 4% for patients with acinar prostate cancer. In this series, metastases were seen in 11% of DACs, as compared with 4% of acinar prostate cancers . For these reasons, it is recommended that prostate cancer showing any component of DAC should be treated as high‐risk disease, owing to its potential to spread locally and the likelihood of the development of metastatic disease …”
Section: Discussionmentioning
confidence: 88%
“…There was consensus that a Gleason score of at least 4 + 4 = 8 be given to ductal carcinomas, but 27% of respondents would not give a Gleason score to this variant. The recent literature agrees with ISUP 2005 that a score of 4 + 4 = 8 should be assigned . This is in contrast to small‐cell carcinomas, which were graded by 24% of respondents despite the ISUP consensus that a Gleason score should not be given for this tumour type, essentially to ensure that cases were treated by systemic chemotherapy …”
Section: Discussionmentioning
confidence: 92%
“…In addition, SMC4/condensin interacts with the genomic transcriptional insulator CTCF, and thus may be required for oncogenic gene silencing (48). SQLE is a cholesterol biosynthesis enzyme that has been implicated in several cancers other than prostate, and, interestingly, is located in the chromosome 8q24 Myc oncogene amplicon (49)(50)(51). SQLE knockdown had an impact in LNCaP-AR but not DU145 cells, which is likely reflective of the much more significant role of steroid hormone signaling in LNCaP-AR cells.…”
Section: Discussionmentioning
confidence: 99%